A brief history of RT-PCR and our laboratory experience with SARS-CoV-2 analyses using RT-PCR - Naci Omer Alayunt (Jurnal Teknologi Laboratorium, 2022)
Polymerase Chain Reaction (PCR) is in vitro replication that allows accelerated amplification of certain sequences in small DNA fragments. A sensitive technique, only traces of DNA are needed for PCR to produce enough copies to be analyzed. In molecular diagnostic laboratories, rRT-PCR technique is applied to find target RNAs for the diagnosis of specific pathogens. Although the rRT-PCR method, which has high specificity and moderate sensitivity, is accepted by WHO as the gold standard test for the confirmation of COVID-19, there are many negative comments about this method that should be considered. While diagnosing SARS-CoV-2, it is possible to say that real-time PCR (RT-PCR) analysis is still valid but not sufficient to quickly distinguish similar infections. For this reason, there is a need for new analysis methods and new RT-PCR studies to be performed with newly developed unique rapid tests.